The Effect of Career Development and Leadership Style on Turnover Intention with Job Satisfaction as a Variable - Rachman, Fajar Arif; Iqbal, M. Ali (International Journal of Education, Information Technology, and Others, 2025)
This study aims to determine the effect of Career Development and Leadership Style on Turnover Intention with Job Satisfaction as a mediating variable at PT ABC. The study uses a quantitative approach with a causal descriptive design. The population of the study was all permanent employees of PT ABC, with a simple random sampling technique, resulting in 100 respondents. Data were collected through questionnaires and analyzed using the Structural Equation Modeling (SEM)-Partial Least Square (PLS) method. The results showed that Career Development and Leadership Style have a significant positive effect on Job Satisfaction. Career Development and Job Satisfaction have a significant negative effect on Turnover Intention. Leadership Style have a not significant negative effect on Turnover Intention. In addition, Career Development and Leadership Style indirectly affect Turnover Intention through Job Satisfaction. This study provides theoretical contributions to the human resource management literature and practical implications for improving the effectiveness of HR management at PT ABC.